The Corfu Criminal Court Archive - Dimitriou, Yanna (Moderna arhivistika, 2021)
This article* examines the encounters of the Ionian people with criminal justice system during the period from 1815 to 1864, when the Ionian Islands were a British protectorate. Drawing on data from cases of the Criminal Court Archives of Corfu for the first time, it argues that criminality mostly concerned the lower social classes and was not very common. Using violence as a lens, the paper primarily focuses on Corfu’s criminal justice system and offers quantitative and qualitative evidence on which further comparative studies of the history of law and crime in Greece and Europe at that time may be based.
Keywords: archives; arhiv; Corfu; criminal court; devetnajsto stoletje; kazensko sodišče; Krf; nineteenth century